Exploring the Nursing Professional Self-Concept of Nursing Interns in China: Current Status and Influencing Factors (International Journal of Nursing Education, 2025)
Objective. This study examines the current self-concept of nursing professionals among intern nursing students, and aims to identify the influencing factors and explore strategies for stabilizing and fostering the positive development of nursing teams. Methods 156 intern nursing students from a tertiary hospital in Beijing were selected as the survey subjects by convenient sampling, the questionnaire survey was carried out using the general information questionnaire and the nursing professional self-concept scale. Results The total score of the professional self-concept scale of intern nursing students was (83.50±13.43), the average score of each item was (2.78±6.71),among the five dimensions, the satisfaction score was the highest (20.89±3.35),indicating that interns generally value their professional identity and derive fulfilment from clinical practice. The professional skills score (18.33±4.49),suggests adequate competence in technical aspects, whereas the lowest score was observed in communication (11.93±1.75), suggesting that insufficient communication skills may hinder effective patient interactions and collaborative team work. There were statistically significant differences in nursing professional self-concept scores among intern nursing students based on gender, leadership roles, only-child status, whether nursing was their chosen major, and personality type. Conclusion Intern nursing students are at a moderate level of self-concept in the nursing profession. Nursing educators should provide a supportive and encouraging learning environment for interns, and improve their professional self-concept by combining theoretical learning and practical experience, so as to continuously stabilize and expand the nursing workforce in China .
Keywords: Nursing interns; Self-concept; Influencing factors